The Pupillary Response of the Common Octopus (Octopus vulgaris) - Soto, Cecilia; Kelber, Almut; Hanke, Frederike D. (Frontiers in Physiology, 2020)
Cephalopods have very conspicuous eyes that are often compared to fish eyes. However, in contrast to many fish, the eyes of cephalopods possess mobile pupils. To increase the knowledge of pupillary and thus visual function in cephalopods, the dynamics of the pupil of one of the model species among cephalopods, the common octopus (Octopus vulgaris), was determined in this study. We measured pupillary area as a function of ambient luminance to document the light and dark reaction of the octopus eye. The results show that weak light (less than 1 cd/m2) is enough to cause a pupil constriction in octopus, and that the pupil reacts fast to changing light conditions. The t50-value defined as the time required for achieving half-maximum constriction ranged from 0.45 to 1.29 s and maximal constriction from 10 to 20 % of the fully dilated pupil area, depending on the experimental condition. Axial light had a stronger influence on pupil shape than light from above, which hints at a shadow effect of the horizontal slit pupil. We observed substantial variation of the pupil area under all light conditions indicating that light-independent factors such as arousal or the need to camouflage the eye affect pupil dilation/constriction. In conclusion, the documentation of pupil dynamics provides evidence that the pupil of octopus is adapted to low ambient light levels. Nevertheless it can quickly adapt to and thus function under brighter illumination and in a very inhomogeneous light environment, an ability mediated by the dynamic pupil in combination with previously described additional processes of light/dark adaptation in octopus.